2024
DOI: 10.1177/03915603241236361
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and antibiotic resistance in community- and hospital-acquired urinary tract infections among adults: Experience from a large tertiary care center in a developing country

Aya Herbawi,
Adham Abu Taha,
Banan M. Aiesh
et al.

Abstract: Background: It is important to note that the causative agents and patterns of antibiotic resistance vary between urinary tract infections (UTIs) acquired in the community and those acquired in a hospital setting. Therefore, the aim of this study was to compare the types of organisms and patterns of antibiotic resistance in adult patients with community-acquired urinary tract infections (CA-UTIs) and hospital-acquired urinary tract infections (HA-UTIs). Methods: Retrospectively, we collected urine samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Similar to a very recently published study, we found a high rate of ESBL positivity and resistance to other antibiotic classes (fluoroquinolones, sulfonamides, and aminoglycosides) in both community-onset and hospital-acquired UTI cases ( Herbawi et al, 2024 ). Carbapenem resistance was also detected in 11.9% of cases with ESBL positivity.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to a very recently published study, we found a high rate of ESBL positivity and resistance to other antibiotic classes (fluoroquinolones, sulfonamides, and aminoglycosides) in both community-onset and hospital-acquired UTI cases ( Herbawi et al, 2024 ). Carbapenem resistance was also detected in 11.9% of cases with ESBL positivity.…”
Section: Discussionsupporting
confidence: 90%